2018
DOI: 10.1080/13602365.2018.1424227
|View full text |Cite
|
Sign up to set email alerts
|

Toward healthy housing for the displaced

Abstract: The population of people living in temporary settlements after disasters is in the millions and the average stay in these settlements exceeds a decade. This paper reviews the literature on the design of post-disaster relief shelters in order to: establish the state of the art, identify trends and describe the academic activity of the past forty years. The analysis demonstrates that the academic engagement in this topic is limited, with fewer than sixty publications in the past four decades. Displacement camps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…The threat of TC-heat may not be restricted to people affected by loss of AC. Some of the TCs mentioned displaced millions of people, and relief housing may not provide safe refuge from extreme heat 19 . Furthermore, humanitarian operations in the wake of TCs can involve large numbers of non-native personnel, such as the 7,600+ US troops arriving after Cyclone Marian 20 .…”
mentioning
confidence: 99%
“…The threat of TC-heat may not be restricted to people affected by loss of AC. Some of the TCs mentioned displaced millions of people, and relief housing may not provide safe refuge from extreme heat 19 . Furthermore, humanitarian operations in the wake of TCs can involve large numbers of non-native personnel, such as the 7,600+ US troops arriving after Cyclone Marian 20 .…”
mentioning
confidence: 99%
“…The environmental impact of the aid shelters has been highlighted as a clear knowledge gap by Ramboll and Save the Children [8], and the need for further research is amongst their recommendations. The same gap was highlighted by Albadra, Coley and Hart [9] as their literature survey showed that in the past 38 years, only 60 academic papers have been published on the subject of 'emergency or temporary shelters', and only nine of them addressed the shelters' life cycle sustainability or environmental impacts.…”
Section: Introductionmentioning
confidence: 84%
“…Scholarly classification of shelters is diverse. Albadra, Coley and Hart [9] categorized the shelters in terms of their manufacturing approach or location into 'transportable shelters' and 'built on-site shelters'. They clarify that transportable shelters include any shelter that is manufactured off-site and then shipped to the intended location.…”
Section: Shelter Typologiesmentioning
confidence: 99%
“…For the 'adapt-a-design' workshops, four main shelter typologies were identified through a literature review (Albadra et al, 2018;Felix et al, 2013;IFRC, 2013). These were: Deployable, in which shelters are delivered in small packaging to site and deployed, for example, a tent.…”
Section: Typologies and Visualization Toolsmentioning
confidence: 99%